Predicting Semen Attributes of Naked Neck and Normally Feathered Male Chickens from Live Performance Traits - Galal, A. (International Journal of Poultry Science, 2006)
The current research was conducted to estimate the prediction equations of semen characters from live performance traits. The performance traits were body weight (BW) and length of shank (SL), comb (CL) and wattle (WL). For this purpose 102 cocks (26 Fayoumi-Nana, 25 Fayoumi-nana, 27 Dandarawi-Nana and 24 Dandarawi-nana) were used. The Fayoumi strain had significantly wider wattle length, higher abnormal sperms and lower coiled tail sperms compared to Dandarawi one. With respect to naked neck (Na) gene, the results indicated that the Na gene had taller CL, wider WL, higher semen volume and lower PSV and higher abnormal sperms compared to normally feathered genotype. In all genetic groups, the coefficients of sample correlation between the body weight and PSV were highly positive and statistically significant. Also, both PSV and abnormal sperms were significantly correlated with BW, CL and WL. Within Dandarawi strain, the BW, CL and WL are good predictors for semen volume in Nana genotype. However, BW alone is good predicator of semen volume in nana genotype. Moreover, within Fayoumi strain, the BW and WL are good predicators for semen volume in Nana genotype. Also, the CL alone is a good predictor for semen volume in nana genotype. The BW, CL and WL are good predictors for PSV in both Fayoumi-nana (R2 = 0.75) and Fayoumi-Nana (R2 = 0.65). According to the findings in this study, it may be concluded that the body weight and lengths of shank, comb and wattle are good predictors of semen attributes in chickens. Moreover, the accuracy of prediction equations (R2) increased with the presence of naked neck (Na) gene, in Fayoumi strain, but not in Dandarawi one.